Impact of different processing techniques on the key volatile profile, sensory, and consumer acceptance of black truffle (Tuber melanosporum Vittadini). Issue 9 (17th August 2022) - Phong, Win Nee; Sung, Billy; Cao, Zhanglong; Gibberd, Mark R; Dykes, Gary A.; Payne, Alan D.; Coorey, Ranil
Abstract : Abstract: Fresh truffles which include black truffle ( Tuber melanosporum Vittadini) deteriorate and lose aroma rapidly after harvest; therefore, postharvest processing via freeze‐drying or encapsulation is an option to preserve truffle aroma for extended supply. However, the aroma profile that directly affects the truffle quality and consumer acceptance is influenced by processing and producers require processing options that balance processing feasibility with retention of a suitable aroma profile. This study aimed to determine the impact of freeze‐drying and encapsulation on the profile of key volatiles, consumer discrimination, and overall sensory impression (aroma intensity, liking, and acceptability) of processed truffle products compared to the starting material (positive control). The study combined experimental‐scale processing with GC‐MS analysis and consumer sensory evaluation to compare and optimize postharvest processing options. Based on the results, some volatile changes were detected in the processed truffle products compared to the positive control which were aligned with the consumer discrimination (triangle test) and the aroma intensity score (consumer sensory test). Despite some chemical and sensory differences detected, the consumer panel did not have any preference for processed truffle products compared to the positive control. The overall finding indicates the potential value of processing truffles into a natural flavoring ingredient for food application via freeze‐drying or encapsulation, which should be of great interest for the truffle and food industry. According to the correlation analysis, the consumer acceptance of a truffle product may be increased by retaining 1‐octen‐3‐ol and methional, while reducing the amount of p ‐cresol in the product. Practical Application: The postharvest process of turning truffles into a food flavoring ingredient may cause undesirable volatile changes that would directly impact the aroma quality and consumer acceptance of the processed truffle products. Hence, the impacts of freeze‐drying and encapsulation on the chemical and sensory profile of truffles were evaluated in this study. Overall, the results of the concurrent instrument and sensory analysis demonstrated that both freeze‐drying and encapsulation are potential options for processing.